Robust Single Molecule Magnet Monolayers on Graphene and Graphite with Magnetic Hysteresis up to 28 K. (1st September 2021) - Spree, Lukas; Liu, Fupin; Neu, Volker; Rosenkranz, Marco; Velkos, Georgios; Wang, Yaofeng; Schiemenz, Sandra; Dreiser, Jan; Gargiani, Pierluigi; Valvidares, Manuel; Chen, Chia‐Hsiang; Büchner, Bernd; et al.
Abstract: The chemical functionalization of fullerene single molecule magnet Tb2 @C80 (CH2 Ph) enables the facile preparation of robust monolayers on graphene and highly oriented pyrolytic graphite from solution without impairing their magnetic properties. Monolayers of endohedral fullerene functionalized with pyrene exhibit magnetic bistability up to a temperature of 28 K. The use of pyrene terminated linker molecules opens the way to devise integration of spin carrying units encapsulated by fullerene cages on graphitic substrates, be it single‐molecule magnets or qubit candidates. Abstract : Air‐stable fullerene‐based single‐molecule magnet Tb2 @C80 (CH2 Ph) is functionalized with pyrene groups. Self‐assembled monolayers of the derivative on graphite and graphene demonstrate magnetic hysteresis up to 28 K.